Assessment of the performance of off-site recycled bituminous material - 442909 Cornelius, P. D. M.; Edwards, A. C.; Transport and Road Research Laboratory (Great Britain) (Crowthorne, Berkshire : Transport & Road Research Laboratory, 1991)
08